Aerodynamics of curved underbody diffusers using CFD. Issue 205 (October 2020) - Huminic, Angel; Huminic, Gabriela
Abstract: This paper presents new results concerning aerodynamics of a bluff body fitted with non-flat underbody diffusers. For the current study a computational approach is used, taking the advantage that CFD has become a valuable and important tool in road vehicle aerodynamics. There are analyzed two basic shapes, namely circular and the elliptical surfaces. As in previous investigations performed, angle and length of the diffuser are the parameters systematically varied within ranges relevant for a hatchback passenger car. Coefficients of lift and drag are computed and compared with the values obtained for the flat underbody diffuser. In order to get a better overview, 3D maps of both lift and drag coefficients were generated using polynomial interpolation of their values. The results reveal significant improvements concerning the lift generated by body fitted with curved diffusers, which are emphasised by an average growth of the downforce larger than 20%. In addition, for small and moderate angles, and small diffuser lengths, the curved diffusers lead also to smaller values of drag, compared to the plane diffusers. Thus, short diffusers with curved sections work better from aerodynamic point of view. In terms of vehicles design, short diffusers have also the advantage of small interferences with other underbody components of cars, as rear wheelhouses and rear silencer. In addition, they offer a significant larger cargo space. Highlights: The paper presents new results concerning aerodynamics of a bluff body fitted with curved underbody diffusers, namely circular and the elliptical surfaces. 3D maps of both lift and drag coefficients were generated using polynomial interpolation of their values. The results reveal significant improvements concerning the lift generated by body fitted with curved diffusers. For small and moderate angles, and small diffuser lengths, the curved diffusers lead to smaller values of drag, compared to the plane diffusers.